Obesity accelerates secondary sexual maturity in girls - Meirina Sari; Endy Paryanto Prawirohartono; Madarina Julia (Indonesian Pediatric Society, 2012)
Background Worldwide incidence of obesity in children isincreasing. Obesity may have many health effects includingadvancement of sexual maturity.Objective T he aim of this study was to assess the timing ofsecondary sexual maturation in obese vs. nonô€„obese girls.Methods Subjects were 105 obese and 105 nonô€„obese girls, aged7 to 8 years who had not entered puberty. Breast and pubic hairgrowth, secondary sexual characteristics, were assessed at baselineand every 4 months for two years. Onset of puberty was defined asTanner stage for secondary sexual maturation of 2: breast Tannerstage II (B2) and/or 2: pubic hair Tanner stage II (P2). Survivalanalyses were used to estimate time to puberty in both groups.Cox regressions were used to analyze possible factors affectingsecondary sexual maturation.Results Mean onset of breast budding (B2) was 7.8 (95% CI 7.7to 7.8) years in obese girls vs. 8.6 (95% CI 8.5 to 8.6) years innonô€„obese girls (P<O.OOl). Mean onset of pub arc he (P2) was 8.7(95% CI 8.6 to 8.8) years in obese girls vs. 9.0 (95% CI 8.9 to 9.0)years in nonô€„obese girls (P<O.OOl). Hazard ratios of obese girlsto experience an earlier secondary sexual maturation at maturitylevel B2, B3 and P2 were 1.34 (95% CI 1.19 to 1.52), 6.91 (95%CI 3.90 to 12.24) and 3.78 (95% CI 2.42 to 5.89), respectively.Conclusions Obesity was associated with earlier onset ofpuberty in girls. Obese girls entered puberty approximately 3 to9 months earlier than their nonô€„obese peers. [Paediatr Indones.2012;52:213-8].